2020
DOI: 10.1038/s41598-020-65908-y
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet worsens Alzheimer’s disease-related behavioral abnormalities and neuropathology in APP/PS1 mice, but not by synergistically decreasing cerebral blood flow

Abstract: Obesity is linked to increased risk for and severity of Alzheimer’s disease (AD). Cerebral blood flow (CBF) reductions are an early feature of AD and are also linked to obesity. We recently showed that non-flowing capillaries, caused by adhered neutrophils, contribute to CBF reduction in mouse models of AD. Because obesity could exacerbate the vascular inflammation likely underlying this neutrophil adhesion, we tested links between obesity and AD by feeding APP/PS1 mice a high fat diet (Hfd) and evaluating beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 69 publications
6
44
0
Order By: Relevance
“…However, the number of cortical plaques were not significantly increased between J20-AD and J20-PCSK9-MIX mice, again confirming findings from the previously discussed study (31). Furthermore, other research has found that high-fat diet in APP/PS1 double transgenic mouse model of AD is able to increase neuropathological changes as well as worsen behavioural abnormalities, however, without any further alterations to CBF (32), as seen in our study.…”
Section: Discussionsupporting
confidence: 92%
“…However, the number of cortical plaques were not significantly increased between J20-AD and J20-PCSK9-MIX mice, again confirming findings from the previously discussed study (31). Furthermore, other research has found that high-fat diet in APP/PS1 double transgenic mouse model of AD is able to increase neuropathological changes as well as worsen behavioural abnormalities, however, without any further alterations to CBF (32), as seen in our study.…”
Section: Discussionsupporting
confidence: 92%
“…It was recently demonstrated that HFD feeding induced the higher entry of 14C-sucrose and 99mTc-albumin into the brains of mice, which indicates BBB disruption ( Salameh et al, 2019 ). It is also important to note that a HFD also caused an increased neuroinflammatory response, increased brain concentration of Aβ species, and exacerbated behavioral deficits in APP/PS1 mice ( Bracko et al, 2020 ).…”
Section: Metabolic Diseases As a Risk Factor For Neurodegenerative DImentioning
confidence: 99%
“…Brains of AD patients commonly exhibit defective insulin signaling [ 38 , 39 ], leading some to argue that AD is actually “Type 3 diabetes” [ 40 ]. Consumption of a hypercaloric diet (e.g., high fat, Western) and metabolic disease have been shown to exacerbate AD pathology and related behaviors in rodent models [ 41 45 ]. Mechanistically, metabolic disease also causes dysregulation of hormones involved in energy balance, as well as increased inflammation and amyloidosis, which is common to AD [ 46 48 ].…”
Section: Introductionmentioning
confidence: 99%